RALF peptides modulate immune response in the moss Physcomitrium patens - Mamaeva, Anna; Lyapina, Irina; Knyazev, Andrey; Golub, Nina; Mollaev, Timur; Chudinova, Elena; Elansky, Sergey; Babenko, Vladislav V.; Veselovsky, Vladimir A.; Klimina, Ksenia M.; Gribova, Tatiana; Kharlampieva, Daria; et al. (Frontiers in Plant Science, 2023)
RAPID ALKALINIZATION FACTOR (RALFs) are cysteine-rich peptides that regulate multiple physiological processes in plants. This peptide family has considerably expanded during land plant evolution, but the role of ancient RALFs in modulating stress responses is unknown. Here, we used the moss Physcomitrium patens as a model to gain insight into the role of RALF peptides in the coordination of plant growth and stress response in non-vascular plants. The quantitative proteomic analysis revealed concerted downregulation of M6 metalloprotease and some membrane proteins, including those involved in stress response, in PpRALF1, 2 and 3 knockout (KO) lines. The subsequent analysis revealed the role of PpRALF3 in growth regulation under abiotic and biotic stress conditions, implying the importance of RALFs in responding to various adverse conditions in bryophytes. We found that knockout of the PpRALF2 and PpRALF3 genes resulted in increased resistance to bacterial and fungal phytopathogens, Pectobacterium carotovorum and Fusarium solani, suggesting the role of these peptides in negative regulation of the immune response in P. patens. Comparing the transcriptomes of PpRALF3 KO and wild-type plants infected by F. solani showed that the regulation of genes in the phenylpropanoid pathway and those involved in cell wall modification and biogenesis was different in these two genotypes. Thus, our study sheds light on the function of the previously uncharacterized PpRALF3 peptide and gives a clue to the ancestral functions of RALF peptides in plant stress response.